2018
DOI: 10.1128/iai.00070-18
|View full text |Cite
|
Sign up to set email alerts
|

Glucan-Chitin Particles Enhance Th17 Response and Improve Protective Efficacy of a Multivalent Antigen (rCpa1) against Pulmonary Coccidioides posadasii Infection

Abstract: Developing an effective and safe recombinant vaccine requires microbe-specific antigens combined with an adjuvant/delivery system to strengthen protective immunity. In this study, we designed and expressed a multivalent, recombinant polypeptide antigen (rCpa1) that consists of three previously identified antigens (i.e., Ag2/Pra, Cs-Ag and Pmp1) and 5 pathogen-derived peptides with high affinity for human MHC II molecules. The purified rCpa1 was encapsulated into four types of yeast cell-wall particles containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(79 citation statements)
references
References 43 publications
4
75
0
Order By: Relevance
“…10 μg of Bl-Eng2 was loaded into GCPs and mice were vaccinated SC or IN three times, two weeks apart as described (Hung et al, 2018), unless otherwise indicated. In some experiments, mice were vaccinated twice either SC with 10 μg Bl-Eng2 formulated in CFA or IFA, or IN with 10 μg Bl-Eng2 in 10% Adjuplex (Empirion, LLC, Columbus OH), two weeks apart.…”
Section: Methodsmentioning
confidence: 99%
“…10 μg of Bl-Eng2 was loaded into GCPs and mice were vaccinated SC or IN three times, two weeks apart as described (Hung et al, 2018), unless otherwise indicated. In some experiments, mice were vaccinated twice either SC with 10 μg Bl-Eng2 formulated in CFA or IFA, or IN with 10 μg Bl-Eng2 in 10% Adjuplex (Empirion, LLC, Columbus OH), two weeks apart.…”
Section: Methodsmentioning
confidence: 99%
“…Current Protocols in Microbiology respectively. These results demonstrate that CD1 mice are more resistant to infection with Coccidioides compared to other mouse strains, such as BALB/c or C57BL/6 (Cox, Kennell, Boncyk, & Murphy, 1988;Hung, Zhang, et al, 2018;Magee & Cox, 1995).…”
Section: Of 26mentioning
confidence: 61%
“…Commonly used and cited laboratory strains are C. posadasii C735 and Silveira (NR-48944) and C. immitis RS (NR-48942) and 2006 (NR-48934). We also recommend the attenuated strain C. posadasii cts2/ ard1/ cts3 , which can be handled in a biosafety level 2 (BSL-2) environment and has been extensively characterized in vitro and in vivo (Hung, del Pilar Jimenez-Alzate, et al, 2014;Hung, Zhang, et al, 2018;Hung, Castro-Lopez, & Cole, 2014;Hung, Gonzalez, Wuthrich, Klein, & Cole, 2011;Mead, Roe, et al, 2020;Mead, Teixeira, Galgiani, & Barker, 2019;Xue et al, 2009). Isolates arrive as a 1-ml glycerol stock that should be stored at -80°C until use.…”
Section: Strategic Planningmentioning
confidence: 99%
“…Identification of immunologically relevant epitopes aids the development of recombinant peptides/polypeptides that can be encapsulated within GPs for generating antigen‐specific protective immunity. For example, recombinant chimeric poly‐epitope antigen (rCpa1), consisting of a combination of three different antigens and five MHC‐II binding pathogen‐derived peptides, was designed for a C. posadasii vaccine . When administered together with a TLR ‐ 9 agonist [DNA containing unmethylated cytosine–phosphate–guanine oligonucleotides (CpG‐ODN)], a non‐protective immune response was induced in a humanized human leucocyte antigen (HLA)‐DR4 transgenic mouse model.…”
Section: Gps With Non‐covalently Encapsulated Antigens For Vaccine Dementioning
confidence: 99%